Franchise sebagai Model Bisnis yang Efektif dalam Ekonomi Modern - Maqfiroh, Siti Annisaul (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to examine the effectiveness of the franchise business model in facing the dynamics of the modern economy. Franchise has become one of the alternative business strategies widely favored because it is considered capable of accelerating business growth with relatively low risk. The main objective of this study is to analyze the advantages of the franchise system, the challenges faced, and its potential in supporting economic growth, especially for small and medium enterprises. The method used in this study is a qualitative descriptive approach with a literature review. Data were collected through the analysis of various literature, scientific articles, business reports, as well as observations of several franchise business practices in the field. The main focus is directed at operational aspects, partnership relationships, and adaptation to technological developments. The results show that franchise is an effective and efficient business model, particularly in terms of business expansion, managerial efficiency, and risk reduction. Additionally, franchises have proven to be more resilient to economic pressures because they are based on a tested system. However, the effectiveness of franchising greatly depends on the quality of the relationship between franchisors and franchisees, as well as their ability to adapt to market changes and technology. Therefore, good management is key to the successful and sustainable operation of franchise businesses.